2018
DOI: 10.1007/s10549-018-4884-x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of anthracyclines and anti-CD47 therapy inhibit invasive breast cancer growth while preventing cardiac toxicity by regulation of autophagy

Abstract: Our experiments indicate that the protective effects observed with CD47 blockade are mediated through upregulation of autophagic flux. However, the absence of CD47 in did not elicit a protective effect in cancer cells, but it enhanced macrophage-mediated cancer cell cytolysis. Therefore, the differential responses observed with CD47 blockade are due to autonomous activation of protective autophagy in normal tissue and enhancement immune cytotoxicity against cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 54 publications
(73 reference statements)
3
48
0
Order By: Relevance
“…Increased expression of CD47 by tumor cells inhibits their phagocytosis, a crucial way in which they evade immune surveillance [19]. Many preclinical studies have shown that abrogation of the SIRPα-CD47 interaction, especially when combined with tumor targeting antibodies or chemo/radiotherapy, promotes cancer cell death and improves survival [19][20][21][22][23][24][25][26][27]. Various biologic agents targeting the SIRPα-CD47 axis, including monoclonal antibodies and decoy receptors, are in early clinical development as cancer immunotherapies [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Increased expression of CD47 by tumor cells inhibits their phagocytosis, a crucial way in which they evade immune surveillance [19]. Many preclinical studies have shown that abrogation of the SIRPα-CD47 interaction, especially when combined with tumor targeting antibodies or chemo/radiotherapy, promotes cancer cell death and improves survival [19][20][21][22][23][24][25][26][27]. Various biologic agents targeting the SIRPα-CD47 axis, including monoclonal antibodies and decoy receptors, are in early clinical development as cancer immunotherapies [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In a mouse model of breast cancer, Feliz‐Mosquea et al . () found significantly reduced metastasis after doxorubicin and CD47 mAb combination therapy.…”
Section: Discussionmentioning
confidence: 90%
“…Combination therapy of doxorubicin and CD47 mAb has shown success in different cancers (Feliz-Mosquea et al, 2018;Iribarren et al, 2019;Li et al, 2018;Wu et al, 2018) but their efficacy in osteosarcoma remains unknown. To our knowledge, our study is the first to evaluate the efficacy of combination therapy with doxorubicin in osteosarcomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between SIRPα on DCs with CD47 on T cells is important for regulating the priming of naive T cells, which then differentiate into T helper cells, or induction of antigen-specific cytotoxic T cell responses by DCs [15]. Current focus on immunotherapy had been targeted toward inhibiting CD47-SIRPα interaction via anti-CD47 or anti-SIRPα antibodies [16].…”
Section: Introductionmentioning
confidence: 99%